Komitmen Dinas Sosial Sumedang Dalam Memberikan Pelayanan Sosial Bagi Lanjut Usia di Kabupaten Sumedang - Achmad, Raden Wilya (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Elderly in Sumedang Regency have their own uniqueness, the growth rate of elderly is getting higher, this requires a special program for the elderly for their survival to stay healthy and productive is very much needed for the elderly to remain productive in old age. This study aims to analyze the role of the Social Service in providing social services to the elderly in Sumedang Regency. The research method uses qualitative studies with descriptive analysis and has informants to support good research results and have novelty. The results of the study show that the Sumedang Regency Social Service has shown a commitment to overcoming the problem of neglected elderly through facilitative, educational, representational, and technical roles. This effort is expected to be able to provide appropriate attention and assistance to neglected elderly, so that they can live their old age with more dignity, be useful to society, and feel appreciated.